The sources and transport model of deep-sea sediment in the Southwest Sub-basin of the South China Sea - Cai, Zhourong; Wang, Xiaoxiang; Zhong, Lifeng; Zhang, Cheng; Sui, Xin (Frontiers in Marine Science, 2024)
Turbidity current deposition belongs to event deposition, which is of great significance to the study of neotectonic movement. However, turbidite deposits are rarely found in deep-sea basins. In this work, the particle size, mineralogy, and geochemistry of 14 deep-sea sediment cores from the Southwest Sub-basin (SWSB) of South China Sea (SCS) and its periphery are used to trace the sources of sediment and reveal the sedimentological and geochemical characteristics of deep-sea sediments. The results show that quartz and feldspar are the main minerals in the core sediments from the SWSB, and there are multiple layers of turbidites. Geochemical analysis reveals that the composition of the core sediments is close to that of the western margin of the SCS and is similar to that of the upper continental crust (UCC) and is inherited from terrigenous sediments. The Sr–Nd isotope results indicate that the sediment provenances of the SWSB are from the Mekong River, Sunda Shelf and Red River, showing the characteristics of multiple sources. Therefore, we propose that terrigenous materials from multiple sources can reach the deep-sea basin of the SWSB, and we also establish a transport model of deep-sea terrigenous sediment. Terrigenous materials were first carried by rivers and surface currents to the continental margins near the SWSB, and fine materials were subsequently transported by surface currents to the deep-sea basin, while coarse materials were subsequently transported by turbidity currents. Turbidity current deposits provide an approach for studying the transport of coarse materials in deep-sea basins of SWSB.